2020
DOI: 10.1111/tmi.13415
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoeal disease knowledge among diarrhoea patient housholds: findings from the randomised controlled trial of the Cholera‐Hospital‐Based‐Intervention‐for‐7‐days (CHoBI7) mobile health program

Abstract: Objective The objective of this study was to evaluate the impact of the Cholera‐Hospital‐Based‐Intervention‐for‐7‐days (CHoBI7) handwashing with soap and water treatment mobile health (mHealth) program on diarrhoeal disease knowledge among diarrhoea patients and their household members in urban Dhaka, Bangladesh. Methods A cluster‐randomised controlled trial of the CHoBI7 mHealth program was conducted among diarrhoea patient households in Dhaka, Bangladesh. Patients were randomised to three arms: standard reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…Despite the global burden of cholera, particularly in sub-Saharan Africa, and the high risk for cholera transmission for the household members of cholera patients, there was limited awareness of cholera transmission and prevention in our study setting in DRC [2,7,8]. This is consistent with previous findings from our research group and other studies conducted in Bangladesh [22][23][24][25]. One study in Zanzibar found that rural women were less likely to be able to specify cholera transmission routes than male counterparts [26].…”
Section: Discussionsupporting
confidence: 89%
“…Despite the global burden of cholera, particularly in sub-Saharan Africa, and the high risk for cholera transmission for the household members of cholera patients, there was limited awareness of cholera transmission and prevention in our study setting in DRC [2,7,8]. This is consistent with previous findings from our research group and other studies conducted in Bangladesh [22][23][24][25]. One study in Zanzibar found that rural women were less likely to be able to specify cholera transmission routes than male counterparts [26].…”
Section: Discussionsupporting
confidence: 89%
“…44 A second cohort study in this population assessed the association between soil-and object-to-mouth contacts and diarrhea prevalence for children under 5 years of age, and found that the odds of having a diarrhea episode in the subsequent month were significantly higher for children with caregiver reports of mouthing feces within the past week. 16 Additional publications document the CHoBI7 mHealth program effect on handwashing with soap while in the hospital, 45 diarrheal disease knowledge, 46 process evaluation for CHoBI7 mobile health program delivery, 47 and recent formative research to develop a CHoBI7 Baby WASH mHealth program targeting safe child feces disposal, improved food hygiene, and safe child mouthing practices. 48 This prospective cohort study, also nested within the recent CHoBI7 mHealth program RCT, adds to this body of literature by investigating the environmental and individual-level risk factors for diarrheal disease among children under 5 years of age residing in slum areas of Dhaka, Bangladesh.…”
mentioning
confidence: 99%
“…One group either examined the signi cance of using this service (S. R. Chowdhury et al, 2020;Kadir, 2020) or assessed how people's perceptions of telehealth use differ from one another (Rahman et al, 2020;Zobair et al, 2020). The effectiveness of telehealth services in improving knowledge and behaviors in particular illnesses/speci c conditions, such as maternal and newborn healthcare (M. E. Chowdhury et al, 2019), hypertension (Jahan et al, 2020), diarrhea (Masud et al, 2020), and diabetes (Morrison et al, 2021) was discussed by the second group of researchers. To our knowledge, however, no previous study has been discussed about comparing knowledge between utilized and unutilized adult individuals.…”
Section: Introductionmentioning
confidence: 99%